The Evolving Landscape of Immunotherapy-Based Combinations for Frontline Treatment of Advanced Renal Cell Carcinoma - Amin, Asim; Hammers, Hans (Frontiers in Immunology, 2019)
Insights into the biology of advanced renal cell carcinoma (aRCC) and the development of agents targeting the vascular endothelial growth factor (VEGF) pathway have positively impacted the outcomes for patients with aRCC for more than a decade. With the recent approval of the combination of two immune checkpoint inhibitors (ICIs), nivolumab and ipilimumab, the era of VEGF monotherapy for untreated advanced renal cell carcinoma is coming to an end for the majority of patients. The rapid evolution of the frontline treatment options for renal cell carcinoma will lead to the approval of other combination immunotherapies - in particular with VEGF inhibitors. Here we review the data for dual immune checkpoint inhibition with nivolumab/ipilimumab as well as the emerging data for ICI plus VEGF inhibitor combinations and discuss the challenges they will pose in the current clinical practice.